Japanese women in grassroots politics: building a gender-equal society from the bottom up - Takao, Yasuo (Routledge Taylor and Francis Group, 2007)
The 1979 UN Convention on the Elimination of all Forms of Discrimination against Women highlights the importance of equal participation of women in public life. Since the early 1960s, women in Japan have voted in elections at significantly higher rates than men. However, Japanese women's equal participation in policy formulation and decision-making lag far behind major democracies. Gender equality is stated under the Japanese constitution, but social practices are far from equal. There are no legal constraints on Japanese women's right to candidacy for public office, but they are far underrepresented in local and national elected assemblies. In 1999 an important landmark in the substantial progress toward gender equality took place when the Japanese government, for the first time, legally denounced the stereotyped division of roles on the basis of gender and described men and women as equal partners. An unprecedented number of legislation, policy changes, and organizational reform at the national level were introduced from this state-led initiation. In the same year, women's grassroots groups were rapidly moving beyond the reach of policy, organizational, and legal changes; they successfully conducted a major nationwide campaign for More Women to Assemblies! and increased the number of elected women representatives at the local level at an unprecedented rate. The purpose of this article is to assess the potential of increased women's political voices in Japan, which can be seen as an alternative way of solving the problems of political disengagement in the male dominated representative democracy. To this end, the article will examine the point of departure in 1999 towards gender free society in Japan, with special emphasis on the importance of grassroots missions in changing the culturally and socially formed mind set of Japanese women.